THE CORRELATION BETWEEN TEST ANXIETY AND ENGLISH MASTERY OF ELEVENTH GRADE STUDENTS OF SMAN 1 BELITANG - Hasanah, Riska; Zuraida, Zuraida; Hayati, Rita
The objectives of this study were to find out whether or not: (1) there were any significant correlation between test anxiety and English mastery and (2) significant contribution of test anxiety on English mastery. The sample of this study was 190 eleventh grade students of SMAN 1 Belitang which was selected by convenience sampling. The data of English mastery were collected through general English test while the test anxiety level were determined by Test Anxiety Inventory (TAI). The data analysis used Pearson Product Moment and regression analysis in SPSS 24 version. Based on the result of correlation analysis, it showed that (1) there was negative significant correlation between test anxiety and English Mastery (r-obtained -0.453 and Ï- value 0.00) and (2) there was 20.5% contribution of test anxiety on English mastery.